Construction and Performance Evaluation of a Flow Meter Based on Thermal Pulse to Measure Plant Sap Flow in Vascular Tissues - M. Teimorzadeh; J. Baradaran Motie; A. Rohani; Y. Selahvarzi (Journal of Agricultural Machinery)
IntroductionNeglecting the water requirements of trees can result in inefficient irrigation practices, leading to either water wastage or drought stress. Effective irrigation management necessitates precise information on the quantity and pattern of water consumption by trees. To achieve optimal irrigation, a reliable method for quantifying plant water needs is crucial, ensuring that trees avoid drought stress. Current methods for assessing tree water requirements often focus on specific components, such as stems or leaves. These techniques typically require manual intervention, which is time-consuming and resource-intensive, thereby restricting their application mainly to research environments.Materials and MethodsA sap-flow meter device was developed to generate a heat pulse in a tree trunk at 15-minute intervals. The device comprises measuring probes, a processing unit, and a data logger. For a comprehensive evaluation, device probes were positioned on the trunk of a Ficus benjamina tree within a controlled environment at two distinct heights. The resulting sap flow through the vascular tissue was then compared to data obtained using the lysimetric method. The Ficus benjamina tree, with a trunk diameter of 3.5 cm and a height of 196 cm, was prepared during the summer of 2022. By measuring the rate of heat pulse dissipation and applying heat transfer principles, sap flow is estimated under the assumption that heat transfer occurs primarily through the sap flow within the vascular tissue. This estimation was achieved using the heat ratio method (HRM).The trunk was triple drilled with holes of 1.5 mm in diameter and 25 mm in depth. Following drilling, the probes were inserted into these holes (Figure 1). To prevent heat transfer from the probes to the surrounding environment, the trunk was wrapped with glass wool insulation. To assess the reliability of the device, the lysimetric method was employed to measure tree transpiration. For this purpose, the soil surface of the pot was covered with cellophane to ensure that evaporation and weight loss of the pot occurred exclusively through the tree's leaves. Hourly measurements of the pot's weight were taken using a digital scale. Changes in the pot's weight indicate the amount of water evaporated, which corresponds to the water transpired by the tree through its vascular tissue.Results and DiscussionThe results showed that the sap-flow meter device slightly overestimates the tree's water consumption compared to the values obtained using the lysimetric method. Sap flow and transpiration follow a similar trend, both escalating throughout the day and reaching their highest levels in the early afternoon. This value reached 17.98 ml h-1 for sap flow and 16 ml h-1 for transpiration (by lysimetric method), followed by a rapid decrease in the late afternoon as the air cooled down. In addition, the results of device measurements showed that spraying water on the leaves lowers both the rate and volume of sap flow. When the canopy becomes wet, the evaporation of water from the leaf surface leads to a drop in the temperature, which in turn significantly slows down the flow of sap.The v1/v2 ratio is not constant over time, making it crucial to choose the right starting point for measurements to ensure effective data acquisition during the device's operational cycle. It is essential to measure (by the device) the difference between temperature probes 40 seconds after heat pulse generation. The sap flow and transpiration followed a similar trend during the experiments. The sap flow and transpiration increased throughout the day, peaking in the early afternoon. On the first day, sap flow reached 17.98 ml h-1, while the second day recorded an even higher rate of 19.75 ml h-1. Correspondingly, the transpiration measured using the lysimetric method peaked at 16 ml h-1, followed by a rapid decline in the late afternoon.ConclusionThe results obtained from the developed device indicate several key findings. Sap flow and transpiration exhibit a similar trend during the test period, with the estimated sap flow value being approximately 30% higher than that obtained using the lysimetric method. The device effectively demonstrated the impact of surface irrigation; spray irrigation influences the sap flow rate such that when the canopy becomes wet, the sap flow rate decreases significantly. Additionally, sap flow and transpiration are positively correlated with air and canopy temperatures, and negatively correlated with relative humidity. Following calibration, the results show that the heat pulse method can accurately and effectively measure sap flow in the vascular tissue of trees.